Probing the interaction of 2,4-dichlorophenoxyacetic acid with human serum albumin as studied by experimental and computational approaches - Tayyab, Saad; Francis, Jaslene Anne; Kabir, Md Zahirul; Ghani, Hamidah; Mohamad, Saharuddin (Elsevier, 2019)
To characterize the binding of a widely used herbicide, 2,4-dichlorophenoxyacetic acid (2,4-D) to the major transporter in human circulation, human serum albumin (HSA), multi-spectroscopic approaches such as fluorescence, absorption and circular dichroism along with computational methods were employed. Analysis of the fluorescence and absorption spectroscopic data confirmed the 2,4-D–HSA complex formation. A static quenching mechanism was evident from the inverse temperature dependence of the KSV values. The complex was stabilized by a weak binding affinity (Ka = 5.08 × 103 M−1 at 298 K). Quantitative analysis of thermodynamic data revealed participation of hydrophobic and van der Waals interactions as well as hydrogen bonds in the binding process. Circular dichroism and three-dimensional fluorescence spectral results showed structural (secondary and tertiary) changes in HSA as well as microenvironmental perturbation around protein fluorophores (Trp and Tyr residues) upon 2,4-D binding. Addition of 2,4-D to HSA was found to improve protein's thermal stability. Competitive displacement results as well as computational analyses suggested preferred location of the 2,4-D binding site as Sudlow's site I (subdomain IIA) in HSA.